Contested secessions rights, self-determination, democracy, and Kashmir - Chandhoke, Neera (New Delhi ; Oxford : Oxford University Press, 2012)
Approaching contested secession and the more Western concept of consensual secession from a political theory perspective, this book focuses on the Kashmir issue as a form of contested secession and examines whether the Kashmiri people have a 'right' to secede.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Secession; Secession -- India -- Jammu and Kashmir